2013
DOI: 10.1103/physrevb.88.075434
|View full text |Cite
|
Sign up to set email alerts
|

Exciton dynamics in atomically thin MoS2: Interexcitonic interaction and broadening kinetics

Abstract: We report ultrafast pump-probe spectroscopy examining exciton dynamics in atomically thin MoS 2 . Spectrally-and temporally-resolved measurements are performed to investigate the interaction dynamics of two important direct-gap excitons (A and B) and their associated broadening kinetics. The two excitons show strongly correlated inter-excitonic dynamic, in which the transient blue-shifted excitonic absorption originates from the internal A-B excitonic interaction. The observed complex spectral response is dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
101
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(112 citation statements)
references
References 44 publications
11
101
0
Order By: Relevance
“…By tuning the probe photon energy through the MoS 2 band gap (both indirect and direct), our UOM measurements show that conduction and valence band states are rapidly populated on a sub-picosecond (ps) time scale in a MoS 2 monolayer after photoexcitation at 3.1 eV, consistent with previous work [14][15][16][17][18] . Pump fluence-dependent measurements reveal that subsequent carrier relaxation in our samples is primarily due to surface-related defects and trap states, not the Auger processes observed in previous measurements on MoS 2 and other semiconductor nanosystems 12,[18][19][20][21][22][23] .…”
supporting
confidence: 71%
See 3 more Smart Citations
“…By tuning the probe photon energy through the MoS 2 band gap (both indirect and direct), our UOM measurements show that conduction and valence band states are rapidly populated on a sub-picosecond (ps) time scale in a MoS 2 monolayer after photoexcitation at 3.1 eV, consistent with previous work [14][15][16][17][18] . Pump fluence-dependent measurements reveal that subsequent carrier relaxation in our samples is primarily due to surface-related defects and trap states, not the Auger processes observed in previous measurements on MoS 2 and other semiconductor nanosystems 12,[18][19][20][21][22][23] .…”
supporting
confidence: 71%
“…The non-equilibrium electrons rapidly scatter towards the conduction band minimum at the K point [14][15][16] , leading to a positive signal for probe photon energies above the bandgap ( ω ≥ 1.9 eV) through state filling (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a more comprehensive study with different excitation fluences, it was found that the more the excited states the more the spectra are shifted to the red. 28 This has been explained as Stark effect due to photoexcited charges, 16,29 inter-excitonic interaction, 30 or band gap renormalization. 31 Additionally, at short delays, the A − and C − photoinduced absorption peaks appear artificially redshifted due to the strong overlap with the A 0 and C 0 bleaching peaks, respectively.…”
Section: Resultsmentioning
confidence: 99%